Valoa tunnelin päässä, varjoja urheilukulttuurissa : kyselytutkimus nykyisille ja entisille suomalaisille naisurheilutoimittajille urheilujournalismin alalla työskentelystä ja alan tasa-arvotilanteesta - Koivula, Oona (2024)
The scarcity of women sports journalists is intertwined with the overall masculinity of the sports world, which has historically been examined, for instance, through depictions of women in sports journalism. However, the description of women sports journalists' own experiences has remained limited in Finnish research, which is why research on women sports journalists was deemed necessary. The purpose of the study was to investigate who the women sports journalists who have worked or are currently working in Finland are, what experiences they have in the field, and how they perceive the gender equality situation within sports journalism. Central to the study were women sports journalists' experiences of how their gender affects their work and career. The study was conducted as an empirical cross-sectional study. The data (n=70) was collected in collaboration with the Sports Journalists' Association of Finland through a questionnaire and by contacting women sports journalists directly and through sports editorial offices via email. The data was analyzed using both quantitative and qualitative methods, as the questionnaire allowed for open-ended responses. The typical women sports journalist was a woman aged 31 to 50 with a master's degree, and with her own background in competitive or elite sports. Most of them worked or had worked as sports journalists in newspapers. Geographically, respondents were predominantly from Uusimaa region. Women sports journalists reported various gender-related challenges when working in the field of sports journalism. These included experiences of belittlement and harassment, primarily from people outside the workplace. Perceptions of the gender equality situation and advancement opportunities in sports journalism varied according to age and work experience. However, negative experiences did not generally affect perceived job satisfaction. The ever-digitalizing working environment brings new challenges, such as gender-based hate speech on social media. Observations of gender-based discrimination and harassment, as well as the gender's impact on career development, are concerning and highlight the presence of gender inequality in the field of sports journalism. The findings are linked to broader societal structures and attitudes that perpetuate gendered differences in the workplace. Although the context of the study is sports journalism, it reflects broader gender equality challenges that extend to many professions and sectors of society.